Blood pressure and clinical outcomes in patients with diabetes and stable coronary artery disease in THEMIS. (3rd October 2022) - Pareek, M; Bhatt, D L; Zheng, L; Lee, J J; Leiter, L A; Simon, T; Mehta, S R; Harrington, R A; Fox, K; Himmelmann, A; Vidal-Petiot, E; Steg, P G
Abstract: Background: Various BP characteristics, e.g., systolic blood pressure (SBP), diastolic blood pressure (DBP), and pulse pressure (PP), as well as heart rate (HR) may affect the risk of both cardiovascular events and bleeding events. However, the exact way in which these characteristics and outcomes are associated among patients with diabetes and stable coronary artery disease (CAD) remains debated. Moreover, it is unknown whether the risks and benefits of intensified antiplatelet therapy in this patient population are affected by their baseline BP and HR. Purpose: To assess the relationship between BP components (including HR) and cardiovascular and bleeding events, and to determine if the effects of ticagrelor vs. placebo varied across the BP and HR spectrum, in patients with diabetes and stable CAD. Methods: THEMIS was a randomized, controlled trial in which 19, 220 individuals ≥50 years of age with stable CAD and type 2 diabetes were randomized to receive either ticagrelor plus aspirin or placebo plus aspirin. Patients with a prior myocardial infarction or stroke, or already on dual antiplatelet therapy, were excluded. The primary efficacy outcome was a composite of cardiovascular death, myocardial infarction, or stroke. The primary safety outcome was TIMI major bleeding. We examined prognostic implications of BP components using 1) restricted cubic splines for the overall trends with outcomes; 2) Cox proportional-hazards regression models with predefined BP component intervals adjusted for demographic, clinical, and laboratory variables; and 3) Cox regression models for the effects of ticagrelor vs. placebo on outcomes across the spectrum of BP component values (test for interaction). THEMIS is registered at ClinicalTrials.gov (NCT01991795). Results: Mean values of baseline BP components were similar between the two study groups. Median follow-up duration was 39.9 months (range 0–57), with 1554 primary efficacy events and 306 primary safety events occurring over the course of the study. All BP components (including HR) displayed various, independent relationships with the tested outcomes. For example, in adjusted spline models, SBP displayed non-linear relationships with the primary outcome, all-cause death, any bleeding, serious adverse events, and intracranial bleeding, and linear relationships with the remaining outcomes. Figure 1 shows the associations of each BP component with the primary efficacy outcome. BP components did not substantially modify the risks and benefits of ticagrelor vs. placebo for the tested outcomes. Conclusions: BP components were independently associated with efficacy and safety outcomes in patients with stable CAD and type 2 diabetes. However, no important modification of BP components on the effect of ticagrelor vs. placebo was detected. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): AstraZeneca